3R Blackboard: A platform for animal and organ sharing. (June 2022) - Czubala, Magdalena A; Eilles, Eva; Staubi, Andreas; Ipseiz, Natacha; Vogt, Michael; Zieglowski, Leonie; Ernst, Lisa; Tolba, René H; Taylor, Philip R; Weiskirchen, Ralf
Since the embedding of the principles of the 3Rs (Replacement, Reduction and Refinement) in national and international regulations on the use of animals, scientists have been challenged to find ways to reduce the number of animals in their research. Here, we present a digital platform, called '3R Backboard', linked to a laboratory animal management system, which facilitates sharing of surplus biological materials from animals (e.g. tissues, organs and cells) to other research teams. Based on information provided, such as genotype, age and sex, other animal workers were able to indicate their interest in collecting specific tissues and to communicate with the person providing the animals. A short pilot study of this approach conducted in a limited academic environment presented strong evidence of its effectiveness and resulted in a notable reduction of the number of mice used. In addition, the use of 3R Blackboard led to resource saving, knowledge exchange and even establishment of new collaboration.